DEPTOR inhibits lung tumorigenesis by inactivating the EGFR-mTOR signals. (28th October 2021) - Gong, Longyuan; Shu, Jianfeng; Chen, Xiaoyu; Pan, Hui; Chen, Guoan; Bi, Yanli; Cui, Danrui; Li, Xufan; Liu, Dian; Wang, Linchen; Wang, Yue; Liu, Pengyuan; et al.
Abstract: DEPTOR plays vital roles in the regulation of cell proliferation and survival by directly modulating the activity of mTORC1/2. However, the physiological role of DEPTOR in lung tumorigenesis, as well as its clinical significance, remains elusive. In this study, we revealed that decreased DEPTOR expression correlated with increased tumor size, poor differentiation, and worse survival in patients with lung cancer. DEPTOR depletion promoted cell proliferation, survival, migration, and invasion in human lung cancer cells. Mechanistically, DEPTOR bound to the kinase domain of EGFR via its PDZ domain to inactivate EGFR signal. Thus, DEPTOR depletion not only directly activated mTORC1/2, but also relieved the inhibition of EGFR to subsequently activate mTOR signals, leading to the induction of cell proliferation and survival. Additionally, activated EGFR-mTOR signals upregulated the expression of ZEB1 and SLUG to induce epithelial-mesenchymal transition, resulting in enhanced migration and invasion. Importantly, Deptor deletion accelerated Kras G12D ;p53 fl/fl -induced lung tumorigenesis and shortened mouse life span via the activation of EGFR-mTOR signals. Collectively, our study demonstrated that DEPTOR acts as a tumor suppressor in lung tumorigenesis, and its reduction may advance the progression of human lung cancer. Highlights: Low DEPTOR levels correlate with increased tumor size, poor differentiation, and worse survival in patients with lung cancer. DEPTOR inactivation promotes cell proliferation and clonogenic survival via activation of the EGFR-mTOR signals. DEPTOR inactivation enhances cell migration and invasion via the induction of ZEB1 and SLUG-dependent EMT. DEPTOR binds to the kinase domain of EGFR via its PDZ domain to inactivate wild-type and mutated/hyperactive EGFR signal. Deptor deletion accelerates Kras G12D ;p53 fl/fl -induced lung tumorigenesis via the activation of the EGFR-mTOR signals in vivo.